1998
DOI: 10.1097/00006534-199804040-00010
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Distraction: Aesthetic and Functional Benefits in Cleft Lip-Palate and Prognathic Patients during Mixed Dentition

Abstract: In the last few years, distraction techniques have been used successfully to correct the hypoplastic human mandible. In patients with cleft lip and palate, normal growth of the maxilla may be impaired by early cleft repair, and many of them do not respond to orthodontic procedures alone. Maxillary distraction is an alternative technique to correct maxillary hypoplasia during mixed dentition. In the last 3 years, the procedure was performed in 38 patients aged between 6 and 12 years; 18 patients had unilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(106 citation statements)
references
References 12 publications
3
96
0
6
Order By: Relevance
“…1,2 The main disadvantages of Delaire face mask therapy are noncompliance due to discomfort, dentoalveolar compensation, and clockwise rotation of the mandible. [3][4][5][6] To reduce these side effects, modified methods of maxillary protraction were developed consisting of (1) maxillary distraction by a rigid external distractor [7][8][9][10][11][12] ; (2) maxillary distraction with a face mask after Le Fort I corticotomy in cleft patients [13][14][15] ; and (3) face mask combined with skeletal anchorage in the upper jaw. [16][17][18] The first two modified methods of maxillary protraction involved Le Fort I corticotomy or osteotomy; the two latter protocols still involved the use of a face mask.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The main disadvantages of Delaire face mask therapy are noncompliance due to discomfort, dentoalveolar compensation, and clockwise rotation of the mandible. [3][4][5][6] To reduce these side effects, modified methods of maxillary protraction were developed consisting of (1) maxillary distraction by a rigid external distractor [7][8][9][10][11][12] ; (2) maxillary distraction with a face mask after Le Fort I corticotomy in cleft patients [13][14][15] ; and (3) face mask combined with skeletal anchorage in the upper jaw. [16][17][18] The first two modified methods of maxillary protraction involved Le Fort I corticotomy or osteotomy; the two latter protocols still involved the use of a face mask.…”
Section: Introductionmentioning
confidence: 99%
“…Molina et al 18 were the pioneers on the use of DO for maxillary advancement, after incomplete horizontal osteotomy of the maxilla, with the aid of application of reverse traction by means of face mask and rubber bands.…”
mentioning
confidence: 99%
“…In the literature this proce- dure is termed distraction, which is defined as a biologic process of new bone formation between surfaces of bone segments that are gradually separated by incremental traction. It has been reported 25 that the advantage of this method is not only its rapidity but also the soft tissue lengthening that occurs during new bone formation, which causes significant changes with less risk of relapse. Distraction osteogenesis has become an important technique in the treatment of maxillary and midfacial hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Rachmiel and others [19][20][21][22][23][24][25] reported that the values related to the treatment effects of surgically assisted protraction of the maxilla using a FM range from 3 to 12 mm in the very short term, compared to conventional FM therapy. In this study we aimed to compare the treatment results of surgically assisted protraction of the maxilla with FM therapy and the results of RMEassisted FM therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation